Synthesis of Micron-Sized NiAl/NiCoAl-Layered Double Hydroxides via a Facile Double Hydrolysis Dropping Method for Supercapacitor Applications - Huang, Xiaowei; Xiang, Wenfeng; Yao, Jiangfeng; Xi, Jianfeng (Frontiers in Energy Research, 2022)
The transition metal-based layered double hydroxides (LDHs) for high-performance supercapacitor applications were synthesized by the double hydrolysis dropping method. We found that the dropping sequence of the cation and anion solutions has a strong influence on the microstructural and electrochemical properties of LDHs. The NiAl LDHs obtained by dropping the Ni2+ solution into the AlO2- solution have obvious layered structures with a particle size of the order of micrometers. They are different from those LDHs prepared by the conventional double hydrolysis method and hydrothermal method. The specific capacity of the NiAl LDHs is about 615 C g−1 at 0.5 A g−1, which is almost twice that of the sample synthesized by the traditional double hydrolysis method (339 C g−1). It is indicated that the performance of the NiAl LDHs is improved by the dropping method. Moreover, an excellent cyclic stability of 83.3% capacitance retention after 1000 cycles at 3 A g−1 was achieved. In addition, the trimetallic NiCoAl LDHs have been synthesized successfully by the dropping method. The results showed that the addition of Co effectively enhanced the electrochemical properties of LDHs. The optimal NiCoAl LDHs display an excellent specific capacity of 990 C g−1 at 0.5 A g−1. This work offers an efficient and facile route, without hydrothermal treatment or adscititious alkali sources, to fabricating LDHs for boosting energy storage capabilities.